Do Satisfied Customers Really Pay More? A Study of the Relationship Between Customer Satisfaction and Willingness to Pay - Homburg, Christian; Koschate, Nicole; Hoyer, Wayne D. (Journal of Marketing, 2005)
Two experimental studies (a lab experiment and a study involving a real usage experience over time) reveal the existence of a strong, positive impact of customer satisfaction on willingness to pay, and they provide support for a nonlinear, functional structure based on disappointment theory (i.e., an inverse S-shaped form). In addition, the second study examines dynamic aspects of the relationship and provides evidence for the stronger impact of cumulative satisfaction rather than of transaction-specific satisfaction on willingness to pay.
UnivIS-Import:2015-03-09:Pub.2005.rw.fbwiwi.migfk.dosati